Successful Utilization of High-Flux Hemodialysis for Treatment of Vancomycin Toxicity in a Child - Timothy Stidham; Pamela D. Reiter; Douglas M. Ford; Gary M. Lum; Joseph Albietz (Case Reports in Pediatrics)
Vancomycin is routinely used for empiric antibiotic therapy in children. Higher-serum-concentration targets for serious infections are now being recommended. This recommendation may result in aggressive dosing with increased potential for toxicity. We report a case of a pediatric patient who developed vancomycin toxicity and associated oliguric renal failure who was treated effectively with high-flux hemodialysis for vancomycin toxicity, clearing serum concentrations of vancomycin by over 75% in only 6 hours (213.2 mcg/mL to 51.8 mcg/mL) with subsequent return to baseline renal function and without adverse sequelae. While not historically considered a viable option for drug removal in cases of toxicity, new high-flux hemodialysis techniques can remove significant percentages of vancomycin in short periods of time.